METODE ASSIGMENT MODEL TERHADAP KEMAMPUAN KINERJA KARYAWAN - Laurencia, Nia (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to determine: differences in employee abilities in solving problems and characters between company environments, differences in abilities between elvina and rico, differences in abilities between rian and soni, helping companies with problems regarding the division of tasks according to their abilities Between employees. The population in this study were office employees who specifically input field data, totaling 4 employees. With a sampling technique using the hungarian method. The research results show that the ability of employees to carry out the tasks given by the company varies in each section and according to their abilities, such as elvina excels in the rico department, rico excels in the departement, soni excelled in his major. The result are obtained from the assigment model or assigment method, the company can see the abilities of each employeed. Keywords: Employee capabilities, assignment methods